Large Area Nanohole Arrays for Sensing Fabricated by Interference Lithography - Valsecchi, Chiara (Sensors (Basel), 2019)
Several fabrication techniques are recently used to produce a nanopattern for sensing, as focused ion beam milling (FIB), e-beam lithography (EBL), nanoimprinting, and soft lithography. Here, interference lithography is explored for the fabrication of large area nanohole arrays in metal films as an efficient, flexible, and scalable production method. The transmission spectra in air of the 1 cm(2) substrate were evaluated to study the substrate behavior when hole-size, periodicity, and film thickness are varied, in order to elucidate the best sample for the most effective sensing performance. The efficiency of the nanohole array was tested for bulk sensing and compared with other platforms found in the literature. The sensitivity of ~1000 nm/RIU, achieved with an array periodicity in the visible range, exceeds near infrared (NIR) performances previously reported, and demonstrates that interference lithography is one of the best alternative to other expensive and time-consuming nanofabrication methods.